Maximizing Network Stability with Automatic Transfer Switch Systems: Memaksimalkan Stabilitas Jaringan dengan Sistem Sakelar Transfer Otomatis - Hadidjaja, Dwi; Pamungkas, Farid Setyo (Procedia of Engineering and Life Science, 2024)
This study examines the functionality and effectiveness of Automatic Transfer Switch (ATS) systems in maintaining power continuity in distributed networks. By employing observational and simulation methodologies, we assessed the operational dynamics of ATS systems when primary power sources fail. The results indicate that ATS systems significantly minimize electricity downtime through swift transitions to backup power, thereby enhancing system reliability. Despite the advantages, certain limitations were identified that could potentially impact system performance if not addressed. These findings have crucial implications for the management of distributed power networks, suggesting improvements in responsiveness to power interruptions and reduction in operational disruptions. Highlights: Seamless Power Switching: ATS guarantees uninterrupted power by swiftly transitioning to backup during outages. Resilient Network: Research underscores ATS effectiveness in minimizing downtime, crucial for robust power distribution. Addressing Limitations: Despite benefits, vigilance is needed to mitigate potential shortcomings for sustained system reliability. Keywords: ATS (Automatic Transfer Switch), Power Supply System, Backup Power